2022
DOI: 10.1111/bjc.12389
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and psychosis: An experience sampling methodology study investigating the inter‐relationship between stress from parenting and positive psychotic symptoms

Abstract: Objectives: There is a strong association between stress and psychotic symptoms, and this study examined the bidirectional nature of this relationship in parents with psychosis, with negative affect as a mediator and a range of other psychosocial factors included as covariates. It also examined whether stress from parenting had a larger impact on psychosis than non-parenting stress. Design:The study used a within-participants repeated measures design, using experience sampling methodology (ESM). ESM is a self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 82 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Consistent with previous research, participants believed that mental health and parenting were intertwined and referred to parents as balancing dual demands (46). In line with existing research, participants indicated that the relationship between parenting stress and mental health was bi-directional and cyclical (30, [47][48][49], highlighting the need for professionals to identify and support parenting stressors. Although the parenting role was typically perceived to be a source of stress, participants highlighted that for some, their identity as a parent was a source of motivation for recovery.…”
Section: Discussionmentioning
confidence: 53%
“…Consistent with previous research, participants believed that mental health and parenting were intertwined and referred to parents as balancing dual demands (46). In line with existing research, participants indicated that the relationship between parenting stress and mental health was bi-directional and cyclical (30, [47][48][49], highlighting the need for professionals to identify and support parenting stressors. Although the parenting role was typically perceived to be a source of stress, participants highlighted that for some, their identity as a parent was a source of motivation for recovery.…”
Section: Discussionmentioning
confidence: 53%
“…Once MCT-F's clinical utility is confirmed, these findings will have important clinical implications. First, the availability of psychological therapy would help these families to deal with these cognitive distortions that are more present in the disease and that have therefore the exacerbation of symptoms and problems in social and family relationships (Radley et al, 2022a). Thus, an intervention such as MCT-F targeting symptoms, social cognition, and metacognition difficulties could improve mothers' awareness of their children's mental states and difficulty in providing adequate care to them and, consequently, prevent loss of custody.…”
Section: Discussionmentioning
confidence: 99%